Trends in the risk of second primary cancer among bladder cancer survivors: a population‐based cohort of 10 047 patients. (17th November 2015) - Muller, Joris; Grosclaude, Pascale; Lapôtre‐Ledoux, Bénédicte; Woronoff, Anne‐Sophie; Guizard, Anne‐Valérie; Bara, Simona; Colonna, Marc; Troussard, Xavier; Bouvier, Véronique; Trétarre, Brigitte; Velten, Michel; Jégu, Jérémie
Abstract : Objectives: To determine whether the risk of second primary cancer (SPC) among patients with bladder cancer (BCa) has changed over past years. Materials and Methods: Data from 10 French population‐based cancer registries were used to establish a cohort of 10 047 patients diagnosed with a first invasive (≥T1) BCa between 1989 and 2004 and followed up until 2007. An SPC was defined as the first subsequent primary cancer occurring at least 2 months after a BCa diagnosis. Standardized incidence ratios (SIRs) of metachronous SPC were calculated. Multivariate Poisson regression models were used to assess the direct effect of the year of BCa diagnosis on the risk of SPC. Results: The risk of new malignancy among BCa survivors was 60% higher than in the general population (SIR 1.60, 95% confidence interval [CI] 1.51–1.68). Male patients presented a high risk of SPC of the lung (SIR 3.12), head and neck (SIR 2.19) and prostate (SIR 1.54). In multivariate analyses adjusted for gender, age at diagnosis and follow‐up, a significant increase in the risk of SPC of the lung was observed over the calendar year of BCa diagnosis ( P for linear trend 0.010), with an SIR increasing by 3.7% for each year (95% CI 0.9–6.6%); however, no particular trend was observed regarding the risk of SPC of the head and neck ( P = 0.596) or the prostate ( P = 0.518). Conclusions: As the risk of SPC of the lung increased between 1989 and 2004, this study contributes more evidence to support the promotion of tobacco smoking cessation interventions among patients with BCa.